Maqbul As Terminology, Its Use And Meaning According To Al-hafiz Ibn Hajar Al-asqalani In His Book Taqrib At-tahzib - Helimy Aris; Mohd Fauzi Mohd Amin (Human Resource Management Academic Research Society, 2024)
Non-Indexed Publication